School-based management implementation and educational outcomes in Philippine public schools: An explanatory sequential inquiry - Ang, Jason V.; Adlit, Marlon F.; Docdoc, Vercelle A.; Comeros, Jihan Sesican; Lagnason-Pacheco, Lycel (Edelweiss Applied Science and Technology, 2025)
Educational quality is enhanced by transferring decision-making to the school level. This study examines SBM implementation across public schools in the Philippines and its influence on educational outcomes, using a mixed-methods approach covering all regions of the country. Quantitative data were gathered from a stratified sample of public elementary and secondary schools (n = 500), including an SBM implementation survey and academic performance indicators (e.g., National Achievement Test scores). Qualitative data were collected through interviews and focus groups with principals, teachers, and parents in selected case schools. Results: Schools with higher SBM implementation levels tended to show better student outcomes, including moderately higher test scores and improved student attendance, compared to schools with low SBM uptake. Statistical analysis indicated a significant positive correlation between SBM practice and school-level academic achievement. Qualitative findings suggest that greater stakeholder participation, local decision-making, and resource flexibility under SBM contributed to these improvements, though challenges such as limited training for school heads and variable community support were noted. The study provides evidence that effective SBM implementation can modestly improve educational outcomes in Philippine public schools. It underscores the importance of capacity building, stakeholder engagement, and supportive policy frameworks to maximize SBM’s impact. Recommendations include strengthening training for school leaders, simplifying administrative processes, and enhancing community involvement to sustain and amplify SBM’s benefits for school effectiveness.